THE PREDICTIVE ROLE OF SELECTIVE LABORATORY PARAMETERS FOR THE OCCURRENCE OF â€œUNWANTED EVENTSâ€ IN ADULTS WITH LAPAROSCOPIC APPENDECTOMY - Milev, Ilija; Velikj Stefanovska, Vesna; Mitevski, Aleksandar; Karagjozov, Panche; Mihailov, Marjan (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
The aim of our study was to assess the potential predictive role of selected laboratory parameters in recognition of laparoscopic appendectomy (LA) associated with unwanted events defined as intraoperative difficulties, conversion to open approach and early postoperative complications.  A multicenter, prospective, clinical study was conducted. 75 randomly selected adults with acute appendicitis were selected as study participants. Twenty-five laboratory parameters were measured for all of them. In 69, LA was performed and in 6 of the patients, a conversion to open appendectomy had to be accomplished. For each patient, we registered the unwanted events in relation to the treatment. Out of 75 participants with LA, 51 (68%) were without and 24 (32%) were with unwanted events. Binary analysis showed significantly higher levels of total bilirubin (p = 0.0228), sodium (p = 0.0161) and C â€“ reactive protein (p = 0.0005) in the group with unwanted events. Multiple logistic regression analysis confirmed the total serum bilirubin as the only independent predictor â€“ OR = 1.079 [p = 0.041, 95% CI = 1.003-1.162]. High levels of C â€“ reactive protein, serum sodium and total serum bilirubin could be indicators of unwanted intraoperative or postoperative course in the patients treated with LA. In such cases it is wise to consider performing the laparoscopic exploration in the presence of an experienced surgeon. Keywords : laparoscopic appendectomy, C- reactive protein, bilirubin, sodium. https://doi.org/10.55302/JMS2251064m